INTEGRASI NILAI-NILAI AL-QUR'AN DAN TAFSIR DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM UNTUK MEWUJUDKAN GENERASI EMAS 2045 - Kurniasih, Dede Dwi; Firmansyah, Mohammad; Inayah, Navisatul; Arrazaq, Zaki (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
This study aims to examine the urgency and strategy of integrating the values ​​of the Qur'an and interpretation into the Islamic Religious Education (PAI) curriculum in order to form the golden generation of Indonesia 2045. Through a literature study approach, this study analyzes various scientific sources, national education policies, and classical and contemporary interpretations to formulate a relevant and contextual curriculum model. The results of the study indicate that the integration of the values ​​of the Qur'an and interpretation systematically can strengthen the spiritual, ethical, and intellectual dimensions of students. The curriculum that adopts prophetic values ​​such as honesty, justice, responsibility, and enthusiasm for learning from the Qur'an has proven effective in forming the character of a generation that is globally competitive but still rooted in Islamic values. The main contribution of this study is to offer a conceptual framework for the PAI curriculum based on the values ​​of the Qur'an and interpretation that can be used as a reference in planning and implementing education towards the vision of Golden Indonesia 2045.